Lethal autoimmune hemagglutination due to an immunoglobulin A autoagglutinin with Band 3 specificity. Issue 8 (2nd April 2014) - Salama, Abdulgabar; Janvier, Daniel; Mayer, Beate; Saison, Carole; Moscatelli, Henriette; Aucouturier, Françoise; Yilmaz, Pinar; Arnaud, Lionel; Wild, Vanessa; Knop, Stefan; Cartron, Jean‐Pierre
<x xml:space="preserve">Abstract</x> Background We describe a patient with a high‐titer warm immunoglobulin (Ig)A autoantibody resulting in death due to hemagglutination rather than to hemolysis. Case Report A 47‐year‐old male patient presented with an intriguing pronounced vascular erythema of the skin. A livedo reticularis associated with cold agglutinin of high thermal amplitude was suspected. The patient's condition unexpectedly and abruptly deteriorated resulting in death 3 days after admission. Study Design and Methods Conventional serologic procedures and immunochemical methods were used. Results Serologic and immunochemical examinations revealed a warm IgA autoantibody of high titer with anti‐Band 3 specificity. Although the patient presented with severe anemia, only mild signs of hemolysis were observed, with no evidence of complement activation. The autopsy revealed an enormous accumulation of agglutinated red blood cells in liver and spleen and a B‐cell lymphoma and cerebral edema. Thus, the patient's death was largely caused by hypoxia related to hemagglutination rather than to hemolysis and/or anemia per se. Conclusion Strongly hemagglutinating antibodies may not only cause immune hemolysis but also hypoxia due to intravascular hemagglutination.